2013
DOI: 10.1371/journal.pone.0056754
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Syncytiotrophoblast Vesicles in Normal Pregnancy and Pre-Eclampsia: Expression of Flt-1 and Endoglin

Abstract: BackgroundThe placental syncytiotrophoblast releases micro and nanovesicles (STBM), into the maternal circulation in normal pregnancy and in increased amounts in pre-eclampsia (PE), which have proinflammatory and antiangiogenic activity and are implicated in PE pathophysiology. Better characterisation of STBM is essential to understand their role in PE.Methods and ResultsSTBM prepared by placental lobe dual perfusion (pSTBM) and mechanical disruption (mSTBM) were analysed by four colour flow cytometry (4CFC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
161
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(172 citation statements)
references
References 45 publications
5
161
1
5
Order By: Relevance
“…12,19,88 These studies have demonstrated an increase in STBEVs in ex vivo placental perfusates in PE in comparison to normal pregnancies. Furthermore, it has been established that STBEVs have a key role in immunomodulation during normal and complicated pregnancies, 12,83,89 and not as purified populations of constituent vesicles, such as exosomes.…”
Section: Placenta-derived Exosomes In Normal and Complicated Pregnanciesmentioning
confidence: 92%
“…12,19,88 These studies have demonstrated an increase in STBEVs in ex vivo placental perfusates in PE in comparison to normal pregnancies. Furthermore, it has been established that STBEVs have a key role in immunomodulation during normal and complicated pregnancies, 12,83,89 and not as purified populations of constituent vesicles, such as exosomes.…”
Section: Placenta-derived Exosomes In Normal and Complicated Pregnanciesmentioning
confidence: 92%
“…40,41 These syncytial knots easily detach from the syncytiotrophoblast, resulting in free, multinucleated aggregates (50-to 150-μm diameter) that are loaded with sFlt1 protein and mRNA, and are capable of de novo gene transcription and translation. 40,42 Other studies using autopsy material have suggested that shed syncytial knots may contribute to circulating sFlt1 in preeclampsia. 43 Because these synytial microparticles are of fetal origin, this process of syncytial microparticle shedding may lead to chimerism, as fetal cells can be retained in the maternal blood and organs for decades after delivery.…”
Section: Biology Of Antiangiogenic State In Preeclampsiamentioning
confidence: 99%
“…Central to the pathophysiology of preeclampsia is ischemia of the placenta (15,16), which leads to the release of soluble factors and micro/nanovesicles (17,18) into the maternal circulation responsible for the clinical signs of preeclampsia: hypertension and proteinuria. These factors have been referred to as "toxins," hence the name "toxemia of pregnancy" (19).…”
Section: Current Therapymentioning
confidence: 99%